Causes of Inflation In The Sudan: An Empirical Analysis - Mansour Ahmed Elmansour ElfakI (Migration Letters, 2022)
The objective of this study is to analyze the factors that led to inflation in the Sudan by applying the cointegration1 model over the period 1994-2016. The ADF results show that all variables stationary at first difference except the GDP. The finding of the study show long run equilibrium between the variables. The result shows that a one-percentage appreciation of nominal exchange rate causes inflation to fall while a similar increase in money supply or in real GDP causes inflation to rise. A one-percentage increase in openness of the economy will not cause an increase in domestic inflation.